Characteristics of market for natural beef in Colorado and northern New Mexico - Grannis, Jennifer, author; Thilmany, Dawn D., author; Sparling, Ed, author; McKenzie, John, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2002)
The objective of this study is to identify those consumers with the highest willingness to pay and identify which properties of ‘natural meats’ are most important to these consumers. Findings show that consumers are willing to pay a higher percentage premium for natural ground beef than for natural beefsteak. We also categorize respondents using the estimated likelihood of paying a premium for natural beef to compare and contrast how several variables differ among potential customers Several demographics (age and income), as well as shopping behavior and types of meat purchased, are significantly associated with those willing to buy at a premium.
March 2002.
Keywords: Natural beef -- Colorado; Natural beef -- New Mexico; Marketing research -- Colorado; Marketing research -- New Mexico